Incidence of subsequent primary cancers and radiation-induced subsequent primary cancers after low dose-rate brachytherapy monotherapy for prostate cancer in long-term follow-up - Vuolukka, Kristiina (BMC Cancer, 2020)
BACKGROUND: As aging is the most significant risk factor for cancer development, long-term prostate cancer (PCa) survivors have an evident risk of developing subsequent primary cancers (SPCs). Radiotherapy itself is an additional risk factor for cancer development and the SPCs appearing beyond 5 years after radiotherapy in the original treatment field can be considered as radiation-induced subsequent primary cancers (RISPCs). METHODS: During the years 1999-2008, 241 patients with localized PCa who underwent low dose-rate brachytherapy (LDR-BT) with I125 and were followed-up in Kuopio University Hospital, were included in this study. In this study the incidences and types of SPCs and RISPCs with a very long follow-up time after LDR-BT were evaluated. RESULTS: During the median follow-up time of 11.4 years, a total of 34 (14.1%) patients developed a metachronous SPC. The most abundant SPCs were lung and colorectal cancers, each diagnosed in six patients (16.7% out of all SPCs). The crude incidence rate of RISPC was 1.7% (n = 4). Half of the SPC cases (50%) were diagnosed during the latter half of the follow-up time as the risk to develop an SPC continued throughout the whole follow-up time with the actuarial 10-year SPC rate of 7.0%. The crude death rates due to metachronous out-of-field SPCs and RISPCs were 50 and 50%, respectively. CONCLUSION: The crude rate of SPC was in line with previously published data and the incidence of RISPC was very low. These results support the role of LDR-BT as a safe treatment option for patients with localized PCa.